Impact of Economic Growth, Inflation on Poverty in North Sumatra Province - Keynes, Benhard; Sirojuzilam, Sirojuzilam; Syafii, M. (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
The ihigh ipoverty irate iis ia istrategic iproblem ifaced iby ithe iNorth iSumatra iregion. ipoverty iis istill ia iserious iproblem, idemonstrated iby ithe ivast imajority iof ipeople iwho istill ido inot imeet itheir ibasic ineeds. ithis istudy iaims ito ianalyze ithe iimpact iof ieconomic igrowth, iinflation iand ipoverty iin ithe inorthern iSumatra iregion. ithe imethod iof iresearch ithat iis iused iis iquantitative iresearch iusing idata iTimes iseries iand icros isection. ithis istudy iuses ia idouble ilinear iregression ianalysis. ibased ion ithe iresults iof iPanel idata iregresi i iwith irandom ieffect imodel, iit iis iknown ithat ieconomic igrowth idoes inot iaffect ipoverty, ibut iinflation ihas ia ipositive iand isignificant ieffect ion ithe ipoverty irate iwith iT-sign iinflation i(-4.984).